Testing the moderating effect of top management support on the sustainability practices of quality costing and life cycle costing - Yasmi, Yasmi; Nirwana, Nirwana; Sundari, Sri; Syamsuddin, Syamsuddin (Edelweiss Applied Science and Technology, 2026)
Sustainability practices in private universities are a series of policies, programs, and activities carried out to ensure environmental, social, economic, and governance sustainability in campus operations. The goal is to create an efficient, responsible, and long-term-oriented educational institution. The use of a strategic costing approach is a cost management approach that focuses on determining and managing costs to support the long-term strategy of higher education institutions. Top management support at private universities is the level of commitment and involvement of top leaders in providing the strategic direction, resources, and encouragement necessary to ensure the successful implementation of institutional programs, including sustainability programs. This study investigates, using strategic costing dimensions that focus on Quality Costing and Life Cycle Costing, the influence on sustainability practices, with Top Management Support (TMS) as a moderating variable. Data were collected from 120 observation questionnaires of private universities in South Sulawesi and processed using Smart-PLS 4. The study shows that TMS strengthens strategic costing in achieving sustainability in private universities. These findings highlight the important role of strategic costing in achieving sustainability and suggest the comprehensive moderating influence of TMS.